Palladium-catalysed reduction of heteroaromatic naphthyl ethers: structural effects on reactivity - Frija, L. (2014)
Tetrazolyl and benzisothiazolyl naphthylmethylic ethers 3 and 4(a–e) are stable crystalline compounds that can be synthesised in high yields by reaction of the corresponding naphthyl methanols (1a–e) with the derivatizing agents 2a and 2b. Experimental conditions for palladium-catalysed hydrogenolysis of ethers 3, 4, with a hydrogen donor and with molecular hydrogen, were investigated. Analysis of the structure and reactivity indicates that naphthylmethylic ethers 3 and 4 are structurally similar to the corresponding benzyloxyderivatives around the ether bond but exhibit different reactivity. Structural analysis for these compounds is based on crystallographic structure determinations, for 5-(2-naphthylmethoxy)-1-phenyltetrazole (3a) and 3-(2-naphthylmethoxy)-1,2-benzisothiazole 1,1-dioxide (4a), and molecular orbital DFT(B3LYP)/6-311G(d) calculations, for all ethers. It can be concluded from this investigation that 5-chloro-1-phenyltetrazole 2a acts as a better derivatizing agent for naphthyl methanols than 3-chloro-1,2-benzisothiazole-11-dioxide 2b, this contrasting with what has been observed with phenols, allylic and benzylic alcohols.